Earthquake-induced interaction between adjacent reinforced concrete structures with non-equal heights. - Karayannis, Chris G. (Earthquake engineering & structural dynamics.)
The influence of the structural pounding on the ductility requirements and the seismic behaviour of reinforced concrete structures designed to EC2 and EC8 with non-equal heights is investigated. Specioal purpose elements of distributed plasticitiy are employed for the study of the columns. Two distinct types of the problem are identified : Type A, where collisions may occur only between storey masses; and Type B, where the slabs of the first structure hit the columns of the other (72 Type A and 36 Type B pounding cases are examined). Type A cases yielded critical ductility requirements for the columns in the pounding area mainly for the cases where the structures were in contact from the beginning of the excitation. In both pounding types the ductility requirements of the columns of the taller building are substantially increased for the floors above the highest contact storey level probably due to a whiplash behaviour. The most important issue in the pounding type B is the local response of the column of the tall structure that suffers the hit of the upper floor slab of the adjacent shorter structure. In all the examined cases this column was in a critical condition due to shear action and in the cases where the structures were in contact from the beginning of the excitation, this column was also critical due to high ductility demands. It can be summarized that in situations of potential pounding, neglecting its possible effects leads to non-conservative building design or evaluation that may become critical in some cases.